Emotional Representation in Video Clips. Feast 'O, Tuan': Roland Barthes's Visual Semiotic Analysis - Anfaisa Ibnu Danan Jaya; Sidiq Setyawan (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
The development of digital technology has transformed music videos into audiovisual media capable of constructing emotional and cultural meanings through visual symbolsm, lighting, gestures, and cinematic narration. One of the Indonesian music videos that strongly represents emotional experiences is